A STEPPING STONE TOWARDS KNOWLEDGE BASED MAINTENANCE - Waeyenbergh, G.; Pintelon, L.; Gelders, L. (The South African Journal of Industrial Engineering, 2011)
Maintenance decision making becomes more and more a management concern. Some decades ago, maintenance was still often considered as an unavoidable side effect of production. The perception of maintenance has evolved considerably. One of the current issues is the maintenance concept, being the mix of maintenance interventions and the general framework for determining this mix. In this paper we describe a modular framework, called Knowledge Based Maintenance, for developing a customised maintenance concept. After describing the general framework and its decision support use, some case experiences are given. This experience covers some elements of the proposed framework.